Зміни показників ліпідного спектра крові залежно від схеми цукрознижувальної терапії у хворих із вперше виявленим цукровим діабетом 2-го типу - Перцева, Т. О.; Маляр, К. Ю. (Clinical Endocrinology and Endocrine Surgery, 2011)
The analysis of dynamics of lipid spectrum in direct connection with the values of compensation of carbohydrate metabolism in patients newly diagnosed with type 2 diabetes, with the experience of the disease up to 3 months and receiving differentiated glucose-lowering therapy according to baseline compensation of carbohydrate metabolism (blood glucose level and glycosylated hemoglobin – HBA1C), and markers of insulin resistance – insulin resistance index HOMA-IR and the severity of abdominal obesity. Assessed the changes in lipid testimony in the context of cardiovascular risk for patients.